2021
DOI: 10.3389/fpsyt.2020.624275
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Cannabinoid Exposure: Emerging Evidence of Physiological and Neuropsychiatric Abnormalities

Abstract: Clinical reports of cannabis use prevalence during pregnancy vary widely from 3% to upwards of 35% in North America; this disparity likely owing to underestimates from self-reporting in many cases. The rise in cannabis use is mirrored by increasing global legalization and the overall perceptions of safety, even during pregnancy. These trends are further compounded by a lack of evidence-based policy and guidelines for prenatal cannabis use, which has led to inconsistent messaging by healthcare providers and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 120 publications
0
31
1
Order By: Relevance
“…It was previously reported that neurons mostly express CBDRs1, and CBDRs2 are predominately found in immune cells including microglia and mast cells [ 183 , 184 ]. Importantly, in utero exposure to exogenous cannabinoids was found to produce deficits in maturation of the foetal brain which are strongly associated with SCH [ 185 , 186 ]. Do these deficits indicate a role of eCB signalling in neurodevelopment since exogenous cannabinoids are able to bind to some other “off-target” receptors?…”
Section: Endogenous Neuromodulators and Pharmacological Agents In Bra...mentioning
confidence: 99%
“…It was previously reported that neurons mostly express CBDRs1, and CBDRs2 are predominately found in immune cells including microglia and mast cells [ 183 , 184 ]. Importantly, in utero exposure to exogenous cannabinoids was found to produce deficits in maturation of the foetal brain which are strongly associated with SCH [ 185 , 186 ]. Do these deficits indicate a role of eCB signalling in neurodevelopment since exogenous cannabinoids are able to bind to some other “off-target” receptors?…”
Section: Endogenous Neuromodulators and Pharmacological Agents In Bra...mentioning
confidence: 99%
“…Of note, although many benefits of phytocannabinoids have been discussed in the context of neurodegenerative diseases and stress relief, the use of Cannabis during critical periods of development such as gestation and lactation as well as during adolescence may be harmful. Prenatal Cannabis exposure predicts fetal growth restriction, preterm delivery, and neonatal intensive care (Nashed et al, 2020). In human term placenta, THC increases AEA levels, which might be detrimental for the balance of trophoblast cells turnover leading to alterations in normal placentation and fetal growth (Maia et al, 2019).…”
Section: Programming Of the Endocannabinoid System During Early Lifementioning
confidence: 99%
“…This sex difference may be driven by sex-specific effects of cannabis. Animal studies found that THC was metabolized to its highly potent compounds in female rats while it was metabolized to various compounds in male rats (Narimatsu et al, 1991). Female adult rats, but not male adult rats, showed symptoms analogous to depression when chronically treated with THC during adolescence (Rubino et al, 2008).…”
Section: Sex Differences In the Relationships Between Cannabis Use And Stressmentioning
confidence: 99%